ANALYSIS OF SINAR MEDAN RESTAURANT OPERATIONAL MANAGEMENT STRATEGY IN THE PPKM PERIOD - Febryola Indra (Universitas Terbuka, 2021)
Sinar Medan Restaurant is one of the restaurants affected by the implementation of PPKM in Indonesia. Because this restaurant has several strategies that can be implemented and planned, so that it can survive until now. Even the condition of the Sinar Medan restaurant has started to recover as before (before the implementation of PPKM). Under these conditions, researchers conducted research on Sinar Medan Restaurant regarding the applicable operational strategy. The purpose of this study was to analyze the condition of the Sinar Medan restaurant during the PPKM period and analyze the management strategy of the Sinar Medan Restaurant during the PPKM period. The purpose of this study was to analyze the condition of the Sinar Medan restaurant during the PPKM period and analyze the management strategy of the Sinar Medan Restaurant during the PPKM period. This research is a qualitative research where the research object chosen by the researcher is Sinar Medan Restaurant located in Gading Serpong. Sinar Medan Restaurant has the concept of a family restaurant. Based on the results and discussions that have been carried out on Sinar Medan Restaurant, it can be concluded that before PPKM Sinar Medan Restaurant never touched social media to do promotions, but now they are doing promotions on social media such as creating Instagram accounts and creating new phone numbers for WhatsApp accounts.